Ethnopharmacology in Treatment of Cancers from Yala Province - Puti, Noor-asma; Neamsuvan, Oratai (Science Essence Journal, 2020)
บทคัดย่อ การศึกษานี้มีวัตถุประสงค์เพื่อสำรวจภูมิปัญญาพื้นบ้านการใช้พืชสมุนไพรรักษาโรคมะเร็ง จากหมอพื้นบ้านจังหวัดยะลา จำนวน 10 คน ดำเนินการศึกษาระหว่างเดือนมกราคมถึงเดือนธันวาคม 2561 โดยการสัมภาษณ์แบบกึ่งโครงสร้าง เพื่อให้ทราบถึงความหมายของโรคมะเร็ง สาเหตุของการเกิดโรค ชนิดและส่วนของพืชสมุนไพรที่ใช้ในการรักษา วิธีการเตรียม และการใช้ยาตามองค์ความรู้พื้นบ้าน จากผลการศึกษา หมอพื้นบ้านส่วนใหญ่เชื่อว่ามะเร็งเกิดจากความไม่สมดุลของธาตุทั้งสี่ ส่งผลให้เกิดความผิดปกติต่อร่างกาย โดยแสดงให้เห็นในลักษณะก้อนเนื้องอกที่ผิดปกติ ลักษณะสำคัญของโรค คือ การอักเสบ ระบบเลือดและน้ำเหลืองเสีย ส่วนสมุนไพรที่ใช้รักษาโรคมะเร็ง พบจำนวน 37 ชนิด จัดอยู่ใน 24 วงศ์ วงศ์พืชที่นิยมใช้มากที่สุด คือ Zingiberaceae วิธีการเตรียมยาที่นิยมมากที่สุด คือ การต้มด้วยน้ำแล้วดื่ม ทั้งนี้สมุนไพรที่นิยมนำมาใช้ในตำรับยามากที่สุด ได้แก่ ขมิ้นชัน (28.57%) และบอระเพ็ด (28.57%) ซึ่งสมุนไพรทั้งสองชนิดนี้เป็นพืชที่มีรายงานเกี่ยวกับความเป็นพิษต่อเซลล์มะเร็ง ดังนั้นข้อมูลเหล่านี้จะเป็นข้อมูลพื้นฐานที่สำคัญสำหรับการศึกษาวิจัยยารักษาโรคมะเร็งที่พัฒนาจากยาสมุนไพรต่อไป ABSTRACT This study aimed to survey local knowledge in using medicinal plants for treating cancer disease according to the ten folk healers in Yala province. The study was carried out during January-December 2018. Information was obtained by semi-structured interviews with 10 key informants to gather the data of definition of cancer, causes of disease, species of plant, plant part used, preparation and use method according to folk wisdom. From the study, most folk healers believed that cancer caused by imbalance of four basic elements resulting in abnormalities in the body by demonstrating tumors. The characteristics of cancer were inflammation (kan aksep) and hematologic and lymphatic disorders. Thirty-seven herbal species belonging to 24 families were used to treat cancer. The most used plant family was Zingiberaceae (5 species). Decoction was preferred method of drug preparation. Drinking was preferred method of drug application. The most popular medicinal plants for cancer disease were Curcuma longa (28.57%) and Tinospora crispa (28.57%); which they had already been tested for their cytotoxic activities. The information gained would be the importance basis for further drug development in cancer treatment.